2013
DOI: 10.3171/2012.9.spine111081
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sagittal balance and lumbar lordosis following less invasive adult spinal deformity surgery with expandable cages and percutaneous instrumentation

Abstract: Object The treatment of adult spinal deformity (ASD) remains a challenge for the spine surgeon. While minimally invasive surgery (MIS) has many favorable attributes that would be of great benefit for the ASD population, improvements in lordosis and sagittal balance have remained elusive in cases involving the MIS approach. This report describes the evolution of an MIS method for treating ASD with attention to sagittal correction. Methods Over an 18-month period 25 patients with thoracolumbar scoliosis were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…32 He shows lumbar lordosis correction of 17.8° and sagittal vertebral axis correction of 3.2 cm over long regional spine constructs. Although statistically significant, these results reveal the inferior segmental power of the TLIF to correct sagittal vertebral axis compared with the single-level lateral MI-LIF with ACR.…”
Section: Traditional Approach Versus Mi-lif With Acrmentioning
confidence: 97%
“…32 He shows lumbar lordosis correction of 17.8° and sagittal vertebral axis correction of 3.2 cm over long regional spine constructs. Although statistically significant, these results reveal the inferior segmental power of the TLIF to correct sagittal vertebral axis compared with the single-level lateral MI-LIF with ACR.…”
Section: Traditional Approach Versus Mi-lif With Acrmentioning
confidence: 97%
“…Percutaneous fusion was introduced with the benefit of smaller incisions and lesser operative trauma in difficult patients [2][3][4][5]. Whether a patient may have an operation or not as necessitated by his or her condition sometimes depends on his co-morbidities and the aggressiveness of available procedures.…”
Section: Introductionmentioning
confidence: 99%
“…27 These parameters are essential for achieving good clinical outcomes after adult spinal deformity. In their retrospective review of 28 consecutive patients who underwent minimally invasive deformity correction and anterior/posterior fusion, Anand et al reported signifi- * Major complications are defined as: 6 "Patient required reoperation, death, blindness, cardiac arrest, deep venous thrombosis, pulmonary embolism, implant failure, neurological deficit, pneumonia, sepsis, stroke, vascular injury, visceral injury, wound dehiscence, deep wound infection, hematoma formation with reoperation and proximal junctional kyphosis with reoperation."…”
mentioning
confidence: 99%